Exploring digital competencies domain and elements for information technology graduates in Malaysia - Asnidatul Adilah Ismail; Razali Hassan (Institute of Advanced Engineering and Science, 2023)
This paper explores the reliability of an instrument to evaluate digital competencies domain and elements for polytechnics’ information technology (IT) graduates in Malaysia towards future industrial revolution using exploratory factor analysis (EFA). This study thereby obtained 146 items from the previous phase (industries experts’ interview) which was later developed according to the study’s objectives. Experts validated the items, and after that, a pilot study was executed with 102 randomly chosen Polytechnics’ IT lecturers from four Malaysian Polytechnics as the respondents for this study. Four domains had been decided which are Personal Effective Competencies, Functional Competencies, Essential Competencies, and Industrial Revolution 4.0 (4IR) Competencies. Elements for each domain were created using the EFA, in which internal reliability was achieved for all construct dimensions. There were 15 elements gained through EFA for those four domains.